PEMANFAATAN DAUN GAMAL SEBAGAI PUPUK ORGANIK CAIR UNTUK MENINGKATKAN PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapa L.) - Novriani, Novriani; Nurshanti, Dora Fatma; Asroh, Ardi; Al'asri, Al'asri (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2019)
To increase the growth and production of pakcoy plants can be done by adding liquid organic fertilizer gamal leaves derived from agricultural waste. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Baturaja University, the time of the study began in September to November 2015. The study used this non factorial complete randomized design, which consisted of five levels of treatment of liquid organic fertilizer which was repeated four times, so it was obtained 20 treatment units. The treatment consisted of  A0: without gamal leaf POC, A1: 10 ml / l water of gamal leaf POC, A2: 20 ml / l water of gamal leaf  POC, A3: 30 ml / l water of gamal leaf POC, A4: Giving of gamal leaf POC 40 ml / l of water (with 200 ml / polybag). The results showed that the administration of gamal leaf POC affected the growth and production of pakcoy plants. Giving 20 ml / l of gamal leaf POC water is the best treatment and can increase pakcoy growth by 20.40% and production by 59.00% when compared to the control treatmentUntuk meningkatkan pertumbuhan dan produksi tanaman pakcoy dapat dilakukan dengan penambahan pupuk organik cair daun gamal berasal dari limbah pertanian. Penelitian ini dilaksanakan di Kebun Percobaan Fakultas Pertanian Universitas Baturaja, waktu penelitian dimulai pada bulan September sampai dengan November 2015. Penelitian ini menggunakan Rancangan Acak lengkap Non Faktorial, terdiri dari lima taraf perlakuan dosis pupuk organik cair diulang sebanyak empat kali, sehingga terdapat 20 unit perlakuan. Perlakuan terdiri A0: tanpa POC daun gamal, A1: pemberian POC daun gamal10 ml/l air, A2: Pemberian POC daun gamal 20 ml/l, A3: Pemberian POC daun gamal30 ml/l air, A4: Pemberian POC daun gamal40 ml/l air (dengan masing – masing penyiraman sebanyak 200 ml/polibeg). Hasil penelitian menunjukkan pemberian POC daun gamal berpengaruh pada pertumbuhan dan produksi tanaman pakcoy. Pemberian POC daun gamal 20 ml/l air merupakan perlakuan terbaik dan dapat meningkatkan pertumbuhan pakcoy sebesar 20,40 % dan produksi sebesar 59,00 % jika dibandingkan perlakuan kontrol.